Among women across worlds : North Korea in the global Cold War - Kim, Suzy, 1972- (Cornell University Press, 2023)
"Excavates the transnational linkages between women of North Korea and the world from the late 1940s to 1975, the year designated by the UN as International Women's Year, and offers a different genealogy of the global women's movement that centers the 'East' and the Third World"-- Provided by publisher.
Keywords: Women -- Korea (North) -- Social conditions -- 20th century.; Feminism -- Korea (North) -- History -- 20th century.; Women's rights -- Korea (North) -- History -- 20th century.; Women and communism -- Korea (North) -- History -- 20th century.; Women communists -- Korea (North) -- History -- 20th century.; Women -- Political activity -- Korea (North) -- History -- 20th century.; Women's rights -- International cooperation -- History -- 20th century.; Korea (North) -- Politics and government -- 20th century.; Femmes -- Corée du Nord -- Conditions sociales -- 20e siècle.; Féminisme -- Corée du Nord -- Histoire -- 20e siècle.; Femmes -- Droits -- Corée du Nord -- Histoire -- 20e siècle.; Femmes et communisme -- Corée du Nord -- Histoire -- 20e siècle.; Femmes communistes -- Corée du Nord -- Histoire -- 20e siècle.; Femmes -- Activité politique -- Corée du Nord -- Histoire -- 20e siècle.; Femmes -- Droits -- Coopération internationale -- Histoire -- 20e siècle.; Corée du Nord -- Politique et gouvernement -- 20e siècle.; SOCIAL SCIENCE / Ethnic Studies / Asian Studies.; Feminism; Politics and government; Women and communism; Women communists; Women -- Political activity; Women -- Social conditions; Women's rights; Women's rights -- International cooperation; Korea (North); North Korea.; Society & culture: general.; Gender studies: women & girls.; Ethnic studies.; Political ideologies.; Society.; 1900-1999; Electronic books.; History